凉血除濕湯의 비만세포 활성화 억제작용 - 김상헌(Sang Hun Kim); 구영선(Young Sun Koo); 진미림(Mi Rim Jin); 김동희(Dong Hee Kim) (동의생리병리학회지, 2006)
Activated mast cells play pivotal roles in allergic and non-allergic inflammatory responses through the release of inflammatory mediators such as histamin, cysteinyl leukotriens, pro-inflammatory cytokines as well as chemokine. We tested whether YHJST, which is clinically prescribed for the treatment of various inflammatory disease including allergic disease, modulate inflammatory reactions in activated mast cells. YHJST decreased the release of histamine and b-hexosamidase in pholbol-12-myristate 13-acetate and/or calcium ionophore A23187 stimulated HMC-1 and RBL-2H3 cells, respectively. Further, the gene expressions of tumor necrosis factor-a, IL-6 and IL-8 were significantly reduced by YHJST. YHJST suppressed powerful induction of NF-kB promoter-mediated luciferase activity. Taken together, these data suggested that YHJST showed it's anti-inflammatory effects through the down-regulation of mast cell activation. KCI Citation Count: 0